Repetition Duration Influences Ratings of Perceived Exertion. Issue 1 (February 2014) - Diniz, Rodrigo C. R.; Martins-Costa, Hugo C.; Machado, Sandra C.; Lima, Fernando V.; Chagas, Mauro H.
This study investigated the effect of different repetition durations on ratings of perceived exertion (RPE) in active muscles (RPE-AM) and the overall body (RPE-O). 19 male volunteers ( M age = 25.4 yr., SD = 3.5) performed strength training protocols with multiple sets matched by the number of sets and repetitions, intensity and rest interval but different repetition durations: 4 sec., 6 sec., or self-paced. Participants were asked to estimate their RPE-AM and RPE-O after each set. Training protocols with a 6-sec repetition duration produced distinct responses on RPE during and after performance compared to 4-sec. and self-paced durations. However, there were no significant differences between 4-sec. and self-paced durations.